Molecular Docking of Turmeric Active Compounds (Curcuma longa L.) against Main Protease in Covid-19 Disease - Nadhiefa Rahmadania Hasnaa; Rosario Trijuliamos Manalu; Subaryanti (East Asian Journal of Multidisciplinary Research, 2022)
Corona Virus Disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2) has become a global epidemic since late 2019. From the results of the analysis, it was found that curcumin compounds have good pharmacokinetics and potential as drugs. The result of visualization of protein-ligand complex showed that curcumin compound had good stability interaction. The molecular docking method for predicting the structure of protein-compound complexes is called protein-ligand docking. Curcumin compounds have a higher affinity than bisdemethoxycurcumin and oseltamivir. The purpose of the study was to find the active compounds contained in the turmeric plant (Curcuma longa L.) which have antiviral activity by inhibiting the SARS-CoV-2 protein.